Model Dan Simulasi Efisiensi Penggunaan Jalan Tol Pekanbaru – Bangkinang – XIII Koto Kampar Dengan Jalan Nasional - Zulfikar, Zulfikar; Nurkholis, Nurkholis; Nofiar, Andri (Innovative: Journal Of Social Science Research, 2024)
This study aims to develop a model and simulation of the efficiency of the use of the Pekanbaru - Bangkinang - XIII Koto Kampar Toll Road compared to the Pekanbaru - Padang national road. The newly built toll road is expected to reduce congestion and increase the efficiency of time and fuel. The research method used is a quantitative approach with modeling and simulation techniques to analyze travel time, speed, distance and fuel used. Data were collected directly by conducting comprehensive trials on the Pekanbaru - Bangkinang - XIII Koto Kampar Toll Road and the Padang - Pekanbaru National Road with an equivalent route. From the data that has been collected, modeling and simulation were carried out to see the level of efficiency of toll road use compared to national roads. The results of this study are expected to provide recommendations for users of the Pekanbaru - Bangkinang - XIII Kota toll road with the Pekanbaru - Padang National Road between the two which is the most efficient in terms of time and fuel consumption accurately.